3D Numerical Simulation of Submerged Vane - Özdemir, Yusuf Can; Üneş, Fatih; Taşar, Bestami; Varçin, Hakan; Gemici, Ercan (International Journal of Environment, Agriculture and Biotechnology, 2022)
When water is taken from desired parts of the natural or regulated riverbed, it is necessary to use river regulating structures to prevent slope and bed erosion. The main project criterion used in this type of river regulation structures is the flow discharge and velocity. Submerged vane structures are an effective and alternative method used to control the flow in river regulation studies. In this study, the river regulation study with submerged wane structures was modeled in 3D with computational fluid dynamics programs (CFD). Submerged vane model results obtained using 3D computational fluid dynamics were evaluated by comparing them with flow velocities obtained from previous submerged vane experimental results. In the generated numerical model, nonlinear and continuity, turbulence model equations were used. The k-ε turbulence model was used for turbulent viscosity. When the results of the current model were compared with the previous experimental study, it was seen that the experimental results and the modeling analysis results were compatible.